Islamic Education Perspective on The Tradition of Celebration of The Night of 1 Suro - Saimima, Khosi; Mudaimin, Mudaimin; Azma, Azma; Nursyam, Nursyam; Samintang, Samintang; Darahim, Muspai (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
This research is a study of the local cultural tradition integration in Islamic education that focuses on the Malam 1 Suro tradition in Petanusugi Village, Indonesia. The research was conducted through a qualitative case study, and data were gathered via in-depth interviewing, participant observation and document analysis. Key informants were also purposively selected and were religious teachers, community leaders, and educational officers. The study examines how Islamic educational structures can be made to align with culturally embedded practices while preserving theological coherence, especially the doctrine of tawhid. Results indicate a range of attitudes between firm support and outright refusal of the tradition, depending on its perceived conformity with Islamic norms. Others, such as congregational prayer or religious sermons, were considered pedagogically compatible with Islamic values. Still, other rituals that include influential gestures, such as tapa bisu (silent puberty fast), had to be revisited in theological terms. The study notes that Islamic educational values, tazkiyatun nafs, muraqabah, silaturahmi, and tauhid, can be found in traditional formats, indicating that, in fact, learning from local wisdom can be placed in the context of character and spiritual education. This research contributes to the literature on contextual Islamic pedagogy and supports the indigenization framework by providing empirical evidence of culturally responsive religious education. Practical implications include the need for policy frameworks that support curriculum adaptation, capacity-building for educators, and the development of an Islamic Cultural Education (ICE) model. These findings affirm that Islamic education can be made more inclusive, dynamic, and contextually relevant through dialogical engagement with local traditions under theological guidance.